2002
DOI: 10.1080/00498250110085827
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of benzydamine by microsomes and precision-cut slices prepared from cattle liver

Abstract: 1. Benzydamine (BZ), a non-steroidal anti-inflammatory drug used in human and veterinary medicine, is not licensed for use in food-producing species. Biotransformation of BZ in cattle has not been reported previously and is investigated here using liver microsomes and precision-cut liver slices. 2. BZ was metabolized by cattle liver microsomes to benzydamine N-oxide (BZ-NO) and monodesmethyl-BZ (Nor-BZ). Both reactions followed Michaelis-Menten kinetics (Km = 76.4 +/- 16.0 and 58.9 +/- 0.4 microM Vmax = 6.5 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…As the K m value (27.18 μ m ) in bovine microsomes is similar to that of swine (20.1 μ m ), we could support the hypothesis of the presence of FMO1 also in the bovine liver, but more evidence is necessary. The K m value was different from that reported in our previous experiment (Santi et al. , 2002): this could be related to the more restricted BZ concentration range adopted (from 2.5 to 250 μ m instead of from 2.5 to 1000 μ m ) to perform the inhibition studies (Kakkar et al.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…As the K m value (27.18 μ m ) in bovine microsomes is similar to that of swine (20.1 μ m ), we could support the hypothesis of the presence of FMO1 also in the bovine liver, but more evidence is necessary. The K m value was different from that reported in our previous experiment (Santi et al. , 2002): this could be related to the more restricted BZ concentration range adopted (from 2.5 to 250 μ m instead of from 2.5 to 1000 μ m ) to perform the inhibition studies (Kakkar et al.…”
Section: Discussioncontrasting
confidence: 86%
“…The microsome incubation protocol was based on the one previously described by Santi et al (2002). The incubation mixture contained 0.2 mg ⁄ mL microsomal protein, 1 mM NADPH and 20 lM MgCl 2 , BZ (2.5, 5, 10, 25, 50, 100 and 250 lM) in a final volume of 0.4 mL with 0.1 M phosphate buffer (pH 7.4).…”
Section: Microsome Incubationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strongly suggests that the heat lability observed for human liver FMO is a consistent characteristic in other preclinical species, and heat lability is a useful and general method for differentiating between FMO and P450 in microsomal incubations. This is used routinely for human liver microsomes (Grothusen et al, 1996), and has been reported for rat, mouse, and cow (Kedderis and Rickert, 1985;Venkatesh et al, 1992;Blake et al, 1995;Ring et al, 1999;Santi et al, 2002). We extend this analysis here for other traditional preclinical species (i.e., dog and monkey).…”
Section: Fisher Et Almentioning
confidence: 83%